2017
DOI: 10.1093/pubmed/fdx018
|View full text |Cite
|
Sign up to set email alerts
|

Can Memory Assessment Services (MAS) in England be categorized? A national survey

Abstract: In the absence of any clear typology, evaluation of MASs will need to focus on the impact of individual structural and process characteristics on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…However, the distribution of these responsibilities across members of staff within a memory service is subject to considerable variation depending on the specific service (Chrysanthaki, Fernandes, Smith, & Black, ). Indeed, memory services have different delivery models across UK regions (Chrysanthaki et al, ; Lindesay, Marudkar, Diepen, & Wilcock, ), resulting in different NHS trust policies and job descriptions. Intuitively, mental health NPs have reported that formal restrictions set out by policies and job descriptions are key factors in the definition of their roles (Maddox et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the distribution of these responsibilities across members of staff within a memory service is subject to considerable variation depending on the specific service (Chrysanthaki, Fernandes, Smith, & Black, ). Indeed, memory services have different delivery models across UK regions (Chrysanthaki et al, ; Lindesay, Marudkar, Diepen, & Wilcock, ), resulting in different NHS trust policies and job descriptions. Intuitively, mental health NPs have reported that formal restrictions set out by policies and job descriptions are key factors in the definition of their roles (Maddox et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It might, therefore, be reasonable to assume that the roles of NPs in memory services are defined by the individual NHS organisations employing them. However, Chrysanthaki et al () found there were such great differences across memory services in England that it was impossible to group them by characteristics, even within the same organisation. Differences in staff numbers, operational performance and postdiagnostic support were particularly prominent (Chrysanthaki et al, ; Lindesay et al, ), suggesting NPs could have vastly different roles depending on which service they work in.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the sample are reported elsewhere (14). The sample reflected the wide diversity of services provided by MASs in terms of size, staffing, provision of post-diagnostic support and followup regimes (17).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, at baseline, all 71 MASs completed organisational questionnaires on their structural and process characteristics. 11…”
Section: Samplementioning
confidence: 99%